GAYATRI AS EPISTEMIC METAPHOR: READING GENDER, POWER, AND INFORMAL CONTROL IN HIGHER EDUCATION MANAGEMENT ACCOUNTING - Rakhmawati, Henny; Purwanti, Lilik (CV. Radja Publika, 2025)
This research is motivated by the need to understand how gender, local culture, and power relations operate beneath the surface of Management Control Systems (MCS) practices in universities, particularly because the dominance of technocratic approaches in the literature has marginalized women’s experiences and cultural symbols such as the Gayatri metaphor. The structural asymmetry in recognizing women’s substantive roles in budgeting reveals an important knowledge gap that requires exploration through a postmodern qualitative approach. This study aims to examine how feminist values and local cultural beliefs influence MCS practices, and how gendered experiences shape meaning and legitimacy within budgetary decision-making processes. Using a qualitative design grounded in a postmodern paradigm and poststructural feminist methodology, the study treats data as discursive constructions produced through interaction rather than objective facts. The analysis employs a deconstructive approach that reads narrative fragments, contradictions, and silences within interviews and documents to uncover the production of meaning and power relations. The findings show that women hold technical-substantive roles in preparing TOR, budget plans (RAB), and activity-based budgeting (RBA), yet remain positioned beneath the symbolic authority of male leaders; that shadow leadership emerges as a dominant pattern enabling women to exercise control without formal legitimacy; and that female leadership introduces control practices that are more deliberative, collaborative, and sensitive to social consequences. These results demonstrate that MCS operates not through formal rationality, but through discursive struggles that construct subjects, meanings, and hierarchical decision structures. The study concludes by emphasizing the need for gender-sensitive and culturally contextual readings of MCS and recommends further exploration of control models grounded in local cultural values.